An investigation into the relationship between particle shape and entrainment. (November 2015) - Wiese, J.; Becker, M.; Yorath, G.; O'Connor, C.
Highlights: Particle shape determined using different techniques. Particles of different shape exhibited different entrainment properties. Shape effects sustained at different particle size and surface charge. Abstract: The effect of particle shape on true flotation has been widely reported. The present paper presents results obtained in investigating the effect of particle shape on the entrainment of particles during the flotation process. Different hydrophilic minerals with particles of varying aspect ratios were used and their shape determined using rheological tests and auto-SEM-EDS (QEMSCAN). Their entrainment properties showed a close relationship to their shape with the recovery due to entrainment increasing as the aspect ratio of the particles increased. The effect of surface charge, by changing pH, and size of particles showed that the effect of shape was sustained at different pHs and particle sizes. Proposals are made to explain these observations in terms of the known relationships between drag coefficients and terminal velocities and shape. Since it has been previously reported that different milling procedures can affect particle shape, these results indicate that it is possible that such different procedures may result in increased entrainment of hydrophilic minerals.